1986
DOI: 10.1063/1.97290
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of Au/InxAl1−xAs Schottky barrier heights

Abstract: The surface barrier heights φbn and room-temperature band gaps Eg of Si-doped InxAl1−xAs layers grown by molecular beam epitaxy on n-type (100) oriented InP substrates have been determined as a function of composition with capacitance versus voltage, internal photoemission, photoluminescence, and double-crystal x-ray rocking curve measurements for 0.45<x<0.55. The results indicate that Eg and φbn are linear functions of x; they also suggest that φbn (0.78)=0 and, for x>0.78, n-type surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…The most promising barrier enhancement technique reported to date has been the growth of a thin layer of undoped latticematched InAlAs [16]- [22] on the InGaAs. InAlAs lattice matched to InP (E, = 1.47 V) has a high Schottky barrier of -0.8 V [23] and a thin layer grown epitaxially on InGaAs has the effect of raising both the electron and hole barriers. Both Organo-Metallic Chemical Vapor Deposition (OMCVD) grown 1161, [18]- [20] and MBE grown [17], [22] material has yielded devices with good performance characteristics.…”
Section: Introduction He Planar Metal-semiconductor-metal (Msm) Phmentioning
confidence: 99%
“…The most promising barrier enhancement technique reported to date has been the growth of a thin layer of undoped latticematched InAlAs [16]- [22] on the InGaAs. InAlAs lattice matched to InP (E, = 1.47 V) has a high Schottky barrier of -0.8 V [23] and a thin layer grown epitaxially on InGaAs has the effect of raising both the electron and hole barriers. Both Organo-Metallic Chemical Vapor Deposition (OMCVD) grown 1161, [18]- [20] and MBE grown [17], [22] material has yielded devices with good performance characteristics.…”
Section: Introduction He Planar Metal-semiconductor-metal (Msm) Phmentioning
confidence: 99%
“…Recently, Lin et al 3 have reported that b of Au contact increased with Al content of In 1Ϫx Al x As. For In 0.52 Al 0.48 As, the use of a contact material which reacts with the semiconductor alloy at the interface to exchange the In atoms for Al atoms could also be used to enhance the Schottky barrier height due to the increase of the Al composition immediately adjacent to the semiconductor.…”
mentioning
confidence: 99%
“…Researches on this ternary compound semiconductor were focused on In 0.52 Al 0.48 As whose lattice constant is matched to InP as well as In 0.53 Ga 0.47 As materials [4,5]. The detailed characteristics of these In 0.52 Al 0.48 As Schottky diodes with different metals were also extensively studied [5][6][7]. However, little has been published regarding the In 0.52 Al 0.48 As material system for microsensor application.…”
Section: Introductionmentioning
confidence: 98%